This site is supported by donations to The OEIS Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A216493 G.f. satisfies: A(x) = 1 + x*A(x)^3 + x^5*A(x)^13. 1
 1, 1, 3, 12, 55, 274, 1444, 7923, 44803, 259325, 1529008, 9151327, 55454164, 339543312, 2097460255, 13055579858, 81803671623, 515552408141, 3265924761595, 20784056808550, 132812937949820, 851847261569025, 5482066256568375, 35388168141000935, 229081418808206500, 1486757986305948780, 9672120691595571320 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,3 LINKS FORMULA G.f. satisfies: A(x) = 1/A(-x*A(x)^5); note that the g.f. of A001764, G(x) = 1 + x*G(x)^3, also satisfies this condition. EXAMPLE G.f.: A(x) = 1 + x + 3*x^2 + 12*x^3 + 55*x^4 + 274*x^5 + 1444*x^6 + 7923*x^7 +... Related expansions: A(x)^3 = 1 + 3*x + 12*x^2 + 55*x^3 + 273*x^4 + 1431*x^5 + 7806*x^6 + 43893*x^7 +... A(x)^13 = 1 + 13*x + 117*x^2 + 910*x^3 + 6578*x^4 + 45643*x^5 + 309127*x^6 +... Given (1) A(x) = 1 + x*A(x)^3 + x^5*A(x)^13, suppose (2) A(x) = 1/A(-x*A(x)^5), then substituting x in (1) with -x*A(x)^5 yields: 1/A(x) = 1 - x*A(x)^5/A(x)^3 - x^5*A(x)^25/A(x)^13, which illustrates that (2) is consistent with (1). PROG (PARI) {a(n)=local(A=1+x); for(i=1, n, A=1+x*A^3+x^5*A^13 +x*O(x^n)); polcoeff(A, n)} for(n=0, 30, print1(a(n), ", ")) CROSSREFS Cf. A216494, A216490, A001764. Sequence in context: A179848 A001764 A171780 * A216494 A120920 A179487 Adjacent sequences:  A216490 A216491 A216492 * A216494 A216495 A216496 KEYWORD nonn AUTHOR Paul D. Hanna, Sep 07 2012 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified October 20 07:17 EDT 2018. Contains 316378 sequences. (Running on oeis4.)